MENTORING IN INTEGRATING HOTS (HIGHER ORDER THINKING SKILLS) IN READING ASSESSMENT - setyowati, yulis; Priyambudi, Surya; Dewanto, Dewanto (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2023)
High Order Thinking Skills (HOTS) have been a topic of discussion among educators in Indonesia in recent years. The awareness of the importance of making test questions that contain HOTS is getting higher after seeing the test results of Indonesian students in several international standardized test events such as the Program of International Student Assessment (PISA) and Trends in International Mathematics and Science Study (TIMSS). It is a fact that PISA test and evaluation, the performance of Indonesian students is still relatively low. Consecutively, the average achievement scores of Indonesian students were ranked 62, 61, and 63 out of 69 countries evaluated. The fact drives this community service is done to enhance teachers’ competence in integrating HOTS into assessment, particularly in reading skills. The aim of this community service is to mentor Senior High School teachers who teach English Subjects with advanced skills to construct item tests that emphasize higher-order thinking skills in reading skills. The methods employed to achieve the goal are mentoring and focus group discussions. The result of this supervision is the increased ability of teachers in developing assessment of reading skills. This can be seen when the initial observation of the assessment of learning collected and analyzed was seen to have HOTS elements only 50%, and after the supervision and Focus Group Discussions were held, the ability was seen to increase to 80%, which means that the reading assessment created by Wijaya Putra High School teachers contain HOTS questions much higher than the initial conditions. In conclusion, this service activity is able to improve teachers' skills in developing HOTS-in reading assessments.